The Culture of Herbal Preparations Among Pregnant Women: A Remedy or a Suicide Potion? A Case Report and Mini Review - P. P. S. Ossei; A. Appiah-Kubi; F. Ankobea-Kokroe; G. Owusu-Asubonteng; W. G. Ayibor; O. K. Aninkora; J. Taylor; E. A. Fenteng; E. Agyemang-Duah; B. M. Agagli; N. Niako (Hindawi Limited, 2020)
In general, use of herbal remedies and preparations is on the ascendency in recent times among the general population and especially in young pregnant women, and this may be very dangerous due to adverse effects and interactions with drugs. A survey by the World Health Organization revealed that 70-80% of the world population resort to nonconventional medicines especially, herbal medicines in their primary healthcare. A lot of work has been done on the positive effects of herbs on the human body but very few publications on the potential side effects of consuming crude herbal preparations especially among pregnant women or the awareness of the medical team of this problem. Herbal remedies may come with many adverse effects and potentially serious interactions with some conventional medications. However, little is known about the dangers associated with consumption of herbal remedies by pregnant patients. Herbal medicines like their orthodox counterparts act through some mechanisms to bring about their curative effects in the body, and this usually goes out of order when these remedies interact with chemical drugs as a result of a combination of both by the victims. This is a case study to review the use of herbal medicine products among pregnant women, especially adolescent girls for abortive purposes, and also attempts to discuss some of the dangers associated with the use of herbal medicinal products together with conventional drugs during pregnancy.